2016
DOI: 10.1111/idj.12225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bacterial contamination of dental unit waterlines and use of a newly designed measurement device to assess retraction of a dental chair unit

Abstract: It is of paramount importance to increase compliance with the standards for controlling DUWL contamination. Routine microbial monitoring and evaluation of retraction are necessary to provide high-quality water for use in dental treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…The frequency of bottle disinfection is a key factor influencing the bacterial contamination of DUWL [13]. The morning purge enables to refresh the Alpron ® solution in the waterlines, and flushing after each patient helps to prevent patient fluids from going back up the DUWL and to avoid the cross-infection of successive patients [15,16]. Nevertheless, considering this long follow-up period, there cannot be any certainty as to the thoroughness of the compliance and the adherence to the procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of bottle disinfection is a key factor influencing the bacterial contamination of DUWL [13]. The morning purge enables to refresh the Alpron ® solution in the waterlines, and flushing after each patient helps to prevent patient fluids from going back up the DUWL and to avoid the cross-infection of successive patients [15,16]. Nevertheless, considering this long follow-up period, there cannot be any certainty as to the thoroughness of the compliance and the adherence to the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological water contamination of DUWL may be due to the water supply [12][13][14], to the retrograde contamination by oral fluids [13,15,16], and to the formation of a biofilm within the tubing promoted by the strong complexity of DUWL, the low water flow in DUWL with a negligible flow at the periphery of the lumen [14,17], the plastic materials constituting the DUWL [18], and the water stagnation during inactivity periods [14,19]. In all cases, the infectious hazard can be limited by the implementation of a preventive strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently bacteria found in this study was B. subtilis. Bacteria of this genus were not only frequent in studies conducted in the 1990s (Garg et al) but also in recent studies as reported by Ji et al (2016) and Szymanska & Sitkowska (2012). However, once they refer only to the genus, it is difficult to compare the amount of this species found by them to the one found in the presented study.…”
Section: Discussionmentioning
confidence: 58%
“…[2][3] The objective of the control infection is to reduce or eliminate the exposure of patients and dental staff members to microorganisms. 4 This way, the biosafety in dentistry can be based However, the literature reports the contamination of dental unit water in an alarming level [6][7] since the first report of this contamination was made by Blake. 8 Moreover, Kelstrup and collaborators 9 were the pioneers in demonstrating the growth of microorganism colonies adhered to dental unit waterline walls, that later would be denominated biofilm.…”
Section: Shortmentioning
confidence: 99%